Socialização organizacional em uma Instituição Federal de Ensino Superior: táticas organizacionais e relações interpessoais como elementos-chave - Bernardino, Dalila Ariana de Abreu (Universidade Federal de São Carlos, 2022)
This work analyzes the socialization process of the administrative civil servant, Administration Assistant position at the Federal University of São Carlos, from organizational tactics and interpersonal relationships with the administrative superior and team members. This study is descriptive with a qualitative and quantitative approach of applied purpose. The research method used was the case study and the technical procedures for data collection were participant observation, document analysis and questionnaire. The questionnaire was applied to administrative civil servants entering from the public notices nº 003/2013 nº 001/2015 to examine the perception of these civil servants about the organizational socialization process and possibilities for improvement. The results indicate a need to reassess the integration process and the training policies for new members. For this, guidelines for reception, development, and monitoring of incoming servants were proposed. Finally, this research aims to understand the organizational socialization relevance as a space for learning and an opportunity to create relationships between newcomers, supervisors, and co-workers.
Organizational socialization in a Federal Institution Of Higher Education: organizational tactics and interpersonal relations as key elements
Keywords: Socialização organizacional; Apoio social; Relações interpessoais; Táticas organizacionais; Instituição Federal de Ensino Superior (IFES); Organizational socialization; Social support; Interpersonal relationships; Organizational tactics; Federal Institution of Higher Education; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DE RECURSOS HUMANOS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA